2018
DOI: 10.3892/etm.2018.6214
|View full text |Cite
|
Sign up to set email alerts
|

Curative effect of artificial femoral head replacement and its effect on hip joint function and complications of senile patients with femoral intertrochanteric fracture

Abstract: Curative effect of artificial femoral head replacement on hip joint function and complications of elderly patients with femoral intertrochanteric fracture were investigated. Eighty patients who were operated for femoral intertrochanteric fractures operation were randomly divided into observation group (n=40) and control group (n=40). The observation group was treated with artificial femoral head replacement, while the control group received internal proximal femur locking plate fixation. In the observation gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…(4) High-concentration oxygen supply for anaesthetic mask was conducted before implantation of bone cement in the surgery to increase oxygen pressure, and enhancing patients' surgical tolerance. (5) The body temperature of the patients were monitored in the surgery, and the upper bodies for these patients were covered with inflatable warm-braw heat preservation carpet for keeping warmth. (6) The patients were asked whether there was discomfort when bone cement was used, including dyspnea, chest pain, panic.…”
Section: Intervention Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…(4) High-concentration oxygen supply for anaesthetic mask was conducted before implantation of bone cement in the surgery to increase oxygen pressure, and enhancing patients' surgical tolerance. (5) The body temperature of the patients were monitored in the surgery, and the upper bodies for these patients were covered with inflatable warm-braw heat preservation carpet for keeping warmth. (6) The patients were asked whether there was discomfort when bone cement was used, including dyspnea, chest pain, panic.…”
Section: Intervention Groupmentioning
confidence: 99%
“…Previous study reported that the incidence of cardiac arrest caused by bone cement implant syndrome was 0.6%-10%, and the mortality was 0.02-0.5% [8]. Predictive nursing is to correctly evaluate the risk of complications, implement targeted nursing, change the previous passive nursing mode, minimize the incidence of complications and improve the prognosis [5,9]. It is of great significance to carry out predictive nursing mode in artificial cemented hemiarthroplasty.…”
Section: The Significance Of Implementing Predictive Nursing Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of gypsum fixation is easy to cause pulmonary infection, venous thrombosis, malnutrition, bedsore, urinary system infection, joint stiffness, and other complications, so choose a surgical remedy is the optimal therapeutic regimen. PFNA, DHS, PFN, Intertan, and Gamma are the most common fixation methods for unstable intertrochanteric fractures [ 6 , 7 ]. Among them, PFNA has the advantages of small incision, less bleeding, and firm fixation, but the operation of PFNA is highly required of skill [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…xation methods for unstable intertrochanteric fractures [6]- [7]. Among them, PFNA has advantages in that only a small incision is required, and it results in less bleeding and rm xation.…”
Section: Introductionmentioning
confidence: 99%